Risk Tolerance and Investor Decision Behavior in MSMEs - Istiqomah, Nuria; Krisnawati, Astrie (AFRE (Accounting and Financial Review), 2021)
This research aimed to determine the effect of neutral information, accounting information, and risk tolerance on individual investors’decision making behavior at productive age in Bandung to invest in Micro, Small, Medium Enterprises (MSMEs) sectors. The phenomenon in this research were explored using quantitative methods. Researchers distributed questionnaires to people of productive age in Bandung city with a total of 400 respondents. The results showed that partially Neutral Information, Accounting Information, and Risk Tolerance variables had a significant effect on the investment decision making of individual investors at productive age in Bandung. The three variables Neutral Information, Accounting Information, and Risk Tolerance also simultaneously have a significant effect on investment decision making of individual investors at productive age in Bandung. Penelitian ini bertujuan untuk mengetahui pengaruh neutral information, accounting information, dan risk tolerance terhadap pengambilan keputusan investasi investor individu pada usia produktif di Kota Bandung untuk berinvestasi pada Sektor Usaha Mikro, Kecil, Menengah (UMKM). Fenomena dalam penelitian ini dieksplorasi dengan menggunakan metode kuantitatif. Peneliti menyebarkan kuesioner kepada masyarakat usia produktif di Kota Bandung dengan jumlah 400 responden. Hasil penelitian menunjukkan bahwa secara parsial variabel neutral information, accounting information, dan risk tolerance berpengaruh signifikan terhadap pengambilan keputusan investasi investor individu pada usia produktif di Kota Bandung. Ketiga variabel neutral information, accounting information, dan risk tolerance juga berpengaruh signifikan secara simultan terhadap pengambilan keputusan investasi investor individu pada usia produktif di Kota Bandung. DOI: https://doi.org/10.26905/afr.v4i2.5979